KOMPETENSI DOSEN, GAMBARAN UMUM ALUMNI DAN PERKEMBANGANNYA - Zainal Abidin; Alamsyah Alamsyah; Baiq Nurul Suryawati (Distribusi - Journal of Management and Business, 2020)
This study aims to determine the development of competence in management department lecturers, the long waiting period for graduates of 2017 alumni in entering the workforce, the suitability of 2017 alumni's educational background with current occupations, the ability to create their own jobs or just waiting and looking for work, graduate competencies in his work, and contributions from the Management Department of Economics and Business Faculty in shaping the competencies of the graduates. The results of the study are the competencies of the Faculty of Management FEB Lecturers in terms of three aspects: 1) The percentage of lecturers who received certification allowances,  FEB lecturers majoring in management as many 96.67%had received lecturer certification, the remaining 3, 33% have not yet received lecturer certification, this means that most have qualified as competent lecturers. 2) In terms of the work behavior of Management FEB lecturers, 95.08 percent behaved very well, and the rest behaved well. 3) a kind Functional Position of Management Department Lecturer.  1 person in Professor, 19 people on Associate Professor, 32 people Position of Lector, and Position of Assistant 9 people. Level of Education FEB lecturers has fulfilled the existing provisions, with the condition that 38.33% have master degree, the remaining 61.67%, 34 people have master degree. For the waiting period of FEB Management alumni in entering the workforce and got jobs before graduating, 23.46% with an average waiting period, 5.8 months before graduating, while 76.54% got jobs after graduation with an average waiting period of 4.58 months. In addition, as many as 19.8% of respondents stated that between their educational background and the first occupation that were occupied very closely, 30.9% stated closely, 21% stated quite closely, 9.9 percent stated less closely, and the remaining 4.9 percent stated not at all.